Virtual cardiac rehabilitation: A rapid shift in care delivery in response to the COVID-19 Pandemic - Clare Koning; Brigitte Friesen; Justin Daigle; Anita Ytsma (The Beryl Institute, 2022)
Cardiac rehabilitation is an integral part of recovery from a critical cardiac life event. This preventative strategy involves exercise rehabilitation, education, lifestyle modification, and self-management coaching - preparing patients for lifelong changes. Prior to the COVID-19 pandemic, these activities were supervised by clinicians in-person, on hospital grounds, and in large groups. However, due to pandemic regulations in Canada imposed in March 2020, all in-person group activities were restricted. Within the first two months of the pandemic, almost half of cardiac rehabilitation services in Canada closed and half of their employees were deployed to other areas. To continue to provide patient care and ensure high-quality patient experience and recovery, cardiac rehabilitation services in Fraser Health, British Columbia rapidly transitioned to exclusively virtual methods of care delivery. Two years later, we are still providing this virtual model of care. This case study reflects on the experience of virtual care delivery of cardiac rehabilitation by participants and health providers. It outlines the process, the challenges, and the outcomes experienced with shifting to a new standard of care. The virtual participation rates showed a slight increase, with a significant reduction in time to access care, and increased adherence to the rehabilitation program. Overall patient satisfaction and provider experience continue to be positive. The consensus is that cardiac rehabilitation should not be optional, even during a global crisis. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens